Clinical and radiological characteristics and 1-year self-reported outcomes from patients with encephalitis and coronavirus disease 2019 - Nathane Braga da Silva Rezende; Fernanda Gomes de Queiroz Barros-Aragão; Talita Pinto; Viviane Tavares Carvalho Crelier; Marcos Ravi Figueiredo; Carlos Otávio Brandão; Andrea Silveira de Souza; Fernanda Tovar-Moll; Gabriel R. de Freitas (Journal of Medical Case Reports)
Abstract Introduction Severe acute respiratory syndrome coronavirus infection is responsible for multisystemic disease and has high transmissibility. It culminated in a pandemic, challenging scientific knowledge and care capacity. Neurological symptoms are highly prevalent, and cases of encephalitis have been described, in both peri- and postinfectious periods. However, pathogenesis and prognosis are unclear. Thus, we aim to describe the clinical findings in cases of encephalitis in patients infected with severe acute respiratory syndrome coronavirus, together with a 1-year follow-up of self-perception of recovery and remaining neuropsychiatric symptoms. Methods This is a retrospective observational study in which patients with cerebrospinal fluid collection and a recent diagnosis of severe acute respiratory syndrome coronavirus infection were screened for encephalitis through analysis of medical records. We describe their clinical and paraclinical findings using descriptive statistics, together with their long-term outcome, through a self-assessment questionnaire. Results Among the 135 patients screened, 11 patients were included. Most of them were admitted for neurological symptoms (73%), and in 63% of cases, those symptoms occurred within the first 7 days of systemic symptoms. Most patients had minor pulmonary involvement assessed on chest computed tomography. On cerebrospinal fluid analysis, the most relevant finding was hyperproteinorrachia. Three patients (27%) had positive changes on magnetic resonance studies. In the outcome analysis, most patients (77%) reported gait difficulties and 66% reported memory and concentration problems. Conclusion Encephalitis associated with severe acute respiratory syndrome coronavirus 2 infection is rare but responsible for chronic sequelae in cognitive and motor aspects. The pathophysiology seems to be associated with both the immune-mediated and inflammatory processes, and the low frequency of paraclinical findings demands a high clinical suspicion.